ChemInform Abstract: A Novel Material of HfScMo2VO12 with Negative Thermal Expansion and Intense White‐Light Emission. Issue 34 (4th August 2016) - Cheng, Yongguang; Liang, Yuan; Ge, Xianghong; Liu, Xiansheng; Yuan, Baohe; Guo, Juan; Chao, Mingju; Liang, Erjun
Abstract: HfScMo2 VO12 is prepared by solid state reaction of stoichiometric amounts of HfO2, Sc2 O3, V2 O5, and MoO3 (air, 973 K, 5 h).